Stringent Internal Quality Control Procedures in Chemical Pathology Lead to Better Performance in External Proficiency Testing - Noreen Atzaz; Mehnaz; Fatima Tuz Zuhra; Siraj Muneer; Haider Ali; Sami Saeed (Journal of Rawalpindi Medical College)
Objective: To assess impact of stringent Internal Quality Control (IQC) checks on performance of proficiency testing